Implementation Of The Rational Unified Process Method In The Web-Based Profile Information System At The Ica Aquarium - Siregar, Roya; Prayudha, Agung Setia (Yayasan Asmin Intelektual Berkah, 2024)
Ica aquarium is a shop that sells ornamental fish in the city of Medan. This store also sells necessities in fish breeding, such as fish feed, aquariums, and aquarium accessories. The products sold in this business can be said to be quite a lot, considering that there are many types of ornamental fish that can be marketed and cultivated. Not only that, fish feed products and aquarium equipment are also available with many different brands. To introduce the types of ornamental fish and products needed by ornamental fish, it can be accompanied by providing a system that introduces the products sold to customers. This aims to make it easier for customers to choose products to buy. Not only that, the information system that will be provided can also help them in managing data, stock, and product marketing. Therefore, this study will create a profile information system at the Ica Aquarium store using the Rational Unified Process (RPU) method in their system development method, with Unified Model Language (UML) as system design and software implementation in coding using PHP and HTML programming languages. Researchers use blackbox testing as information system testing. This research produces a profile information system that is multiuser, besides that It can also provide information about products in the store. That way this profile information system also helps Ica Aquarium to market its products.